Karakteristik Sosial Ekonomi Peternak Sapi Ekstensif di Kecamatan Andolo, Kabupaten Konawe Selatan - Hakim, Muh Haidir; Putri, Anindyaningrum Zainal; Ramadhana, Arga; Irul; Fourthson, Muh. Fathan (Jurnal Informasi, Sains dan Teknologi, 2025)
This study aims to describe the socio-economic characteristics of cattle breeders in Andolo District, South Konawe Regency. The method used is quantitative descriptive with a purposive sampling approach to 40 breeders. The results show that most breeders are of productive age (25–55 years), male, have a high school education, and have more than 10 years of livestock farming experience. The maintenance system used is comprehensive and traditional. This livestock business is a side job with an average ownership of 3 cows of their own. The annual income from large livestock businesses ranges from 5–10 million rupiah, and livestock is generally used as family savings. These findings indicate that cattle farming in this area is still subsistence and has not developed commercially.